5
$\begingroup$

$y\frac{dy}{dx} = x(y^4 + 2y^2 + 1)$

$y = 1$ when $x = 4$

I tired to integrate by substitution, but it doesn't seem to work out.

$\endgroup$
4
$\begingroup$

Write this as

$${1\over 2} 2y {dy\over dx} = x((y^2)^2+2y^2+1)$$

Then you have the LHS is ${1\over 2}{d(y^2)\over dx}=x(y^2+1)^2$

So you get

$${1\over 2}{d(y^2)\over (y^2+1)^2}=x\,dx$$

integrate both sides

$$-{1\over 2}(y^2+1)^{-1}={1\over 2}x^2+C$$

Plugging in, we get $-{1\over 4}=8+C$, so $C=-{33\over 4}$.

We conclude the solution is

$$-{1\over 2}(y^2+1)^{-1}={1\over 2}x^2-{33\over 4}.$$

$\endgroup$
7
  • 1
    $\begingroup$ Well it's like an epiphany, never thought about factoring...Thanks a lot! $\endgroup$ – Ivan Huang Jul 24 '15 at 2:15
  • $\begingroup$ I think $c =\frac{-33}{4}$. $\endgroup$ – John_dydx Jul 24 '15 at 2:20
  • 1
    $\begingroup$ @john yes, thanks! $\endgroup$ – Adam Hughes Jul 24 '15 at 2:35
  • $\begingroup$ Could you explain how you got into the $d(y^2)$ step? I'm learning about this and I couldn't understand that part. $\endgroup$ – YoTengoUnLCD Jul 24 '15 at 2:40
  • $\begingroup$ @yotengounlcd it's the chain rule. $\endgroup$ – Adam Hughes Jul 24 '15 at 5:55
2
$\begingroup$

Notice, we have $$y\frac{dy}{dx}=x(y^4+2y^2+1)$$ $$\frac{y}{y^4+2y^2+1}dy=xdx$$ $$\frac{y}{(y^2+1)^2}dy=xdx$$ Now, integrating both the sides we have $$\int \frac{y}{(y^2+1)^2}dy=\int xdx$$ $$\frac{1}{2}\frac{(y^2+1)^{-1}}{-1}=\frac{x^2}{2}+c$$ $$-\frac{1}{2(y^2+1)}=\frac{x^2}{2}+c$$ Substituting $y=1$ & $x=4$, we get $$\frac{-1}{2((1)^2+1)}=\frac{(4)^2}{2}+c\implies c=\frac{-31}{4}$$ Hence, the solution is $$-\frac{1}{2(y^2+1)}=\frac{x^2}{2}-\frac{31}{4}$$

$\endgroup$
1
  • $\begingroup$ I think $c = \frac{-33}{4}$. $\endgroup$ – John_dydx Jul 24 '15 at 2:16
2
$\begingroup$

To solve this, you can use separation of variables:

$$ y \frac{dy}{dx} = x(y^4+2y^2+1)$$

$$ \frac{y}{y^4+2y^2+1}dy = x\ dx$$

$$ \frac{y}{(y^2+1)^2}= x \ dx$$

Using the substitution $u = y^2+1$, $\frac{du}{dy}= 2y $

$$ \frac{1}{2}\int u^{-2} du= \int x \ dx $$

$$ \frac{-1}{2(y^2+1)} = \frac{x^2}{2} + c$$

where c is a constant of integration.

You can then obtain a value for $c$ using $x =4 \ \text{and}\ y =1$

This should give you $c =\frac{-33}{4}$

Hence, solution:

$$ \frac{2}{y^2+1} =33- 2x^2 $$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.